2014
DOI: 10.1021/la404342d
|View full text |Cite
|
Sign up to set email alerts
|

Simulated Adhesion between Realistic Hydrocarbon Materials: Effects of Composition, Roughness, and Contact Point

Abstract: The work of adhesion is an interfacial materials property that is often extracted from atomic force microscope (AFM) measurements of the pull-off force for tips in contact with flat substrates. Such measurements rely on the use of continuum contact mechanics models, which ignore the atomic structure and contain other assumptions that can be challenging to justify from experiments alone. In this work, molecular dynamics is used to examine work of adhesion values obtained from simulations that mimic such AFM exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 54 publications
0
45
0
Order By: Relevance
“…This results in a supplemental work of adhesion term, which includes the effects of topography as well as the contribution to adhesion from covalent bonds at the interface, both of which can change during loading or sliding. However, other studies showed that continuum contact mechanics may break down at the atomic scale [23][24][25][26][27]. Further, due to the discreteness of atoms at the contact interface, the definition of contact is ambiguous at the atomic scale, which complicates comparison to continuum mechanics predictions [20,28,29].…”
Section: Introductionmentioning
confidence: 99%
“…This results in a supplemental work of adhesion term, which includes the effects of topography as well as the contribution to adhesion from covalent bonds at the interface, both of which can change during loading or sliding. However, other studies showed that continuum contact mechanics may break down at the atomic scale [23][24][25][26][27]. Further, due to the discreteness of atoms at the contact interface, the definition of contact is ambiguous at the atomic scale, which complicates comparison to continuum mechanics predictions [20,28,29].…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogenated amorphous carbon contains a higher fraction of sp 2 carbon and therefore will behave differently from single-crystal diamond. With regard to dispersion forces specifi cally, [ 52 ] a-C:H has a lower number density of atoms as compared to singlecrystal diamond, but the electrical conductivity is much higher, as is the polarizability of atoms. The surface termination and amount of hydrogen on the surface have also been shown to have an effect on work of adhesion.…”
Section: Comparing Work Of Adhesion To Previously Proposed Valuesmentioning
confidence: 99%
“…It was reported that the adhesion hysteresis took place with the occurrence of plastic deformation when the yield point was passed during loading . The hysteresis could originate from the formation of the covalent bonds between the flat plate and asperities during contact process, and larger forces are required to separate the atoms forming the covalent bonds . Representative snapshots for the simulated systems when the plate is brought into contact and pulled back from the substrate with six asperities (shielded by the front ones three asperities cannot be seen; asperity height: 10 Å) are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%